Edukasi dan Pendampingan Diabetes Self-Management Education (DSME) untuk Meningkatkan Pengendalian Gula Darah pada Penderita Diabetes Melitus Tipe II - Putri Ryandini, Tiara; Nurhadi, Mokhamad; Pitaloka, Dyah; Sugiarta, Agus (Universitas Dinamika, 2026)
Diabetes mellitus type II is a global health problem with a steadily increasing incidence, including in Indonesia, where the prevalence has reached 10.9%. One strategy to prevent complications is through Diabetes Self-Management Education (DSME), an educational process aimed at improving patients' knowledge, skills, and motivation to manage their disease independently. This community service activity aims to provide DSME education and assistance to diabetes mellitus type II sufferers so they can optimally control their blood sugar. The activity method is carried out through counseling, group discussions, self-monitoring blood sugar training, and dietary and physical activity assistance. The results of the activity showed an increase in participants' knowledge scores regarding diabetes management based on pre- and post-test results, improved attitudes towards implementing a healthy lifestyle, and increased skills in self-monitoring blood sugar levels. This activity is expected to be a preventive measure in reducing the risk of complications and improving the quality of life for diabetes mellitus type II sufferers.